Effects of medium chain fatty acids to replace zinc oxide and carbadox in nursery pig diets - Pettigrew, Jacob T.; Lerner, Anne B.; Jones, Cassandra K. (My University, 2019)
Increasing regulatory and consumer pressure to reduce antimicrobial use in swine diets is creating a push in finding an alternative product. The objective of this study was to observe the effects of adding dietary amount of zinc oxide, carbodox, and medium chain fatty acids on nursery pig performance. A completely randomized design was conducted with 360 pigs (DNA 200x400; 5.4 ± 0.07 kg; 21 d of age) in a 35-d experiment with 6 pigs/pen and 10 replicate pens/treatment that were fed one of 6 treatments. The treatments were: 1) control; 2) 3,000 ppm ZnO in phase 1 and 1,500 ppm ZnO in phase 2; 3) 50g/ton carbadox; 4) 1% blend of C6:C8:C10; 5) 1% Feed Energy R2 (Feed Energy, Iowa City, IA); 6) 1% FORMI GML (ADDCON, Bitterfeld-Wolfen, Germany). Treatments diets were fed in two phases from weaning to d 19 and a common diet fed as phase 3 from d 20 to 35. With the pen as the experimental unit, data was analyzed using PROC GLIMMIX (SAS version 9.4: Cary, NC). From d 0 to d 19 period, pigs fed ZnO or carbadox had improved (P<0.05) ADG relative to pens with the negative control or R2 diets. While FORMI saw similar results in growth to carbodox with the other MCFA treatments being intermediate. ADFI was higher (P<0.05) for pens fed ZnO relative to the control, C6:C8:C10, or R2 while others were intermediate. Little significance in G:F came from treatment differences (P=0.078). Results of this study suggest ZnO and carbadox are still viable options that producers can use to maximize growth performance in early stages post weaning while FORMI GML can achieve similar growth, whereas other MCFA-based feeds produce variable performance. Therefore, further research must be conducted on other variations of MCFAs to replace ZnO or feed-based antimicrobials.
Keywords: Spring 2019